Phosphatidylcholine (PCL) fortified nano-phytopharmaceuticals for improvement of therapeutic efficacy - Devesh U. Kapoor; Mansi Gaur; Akshay Parihar; Bhupendra G. Prajapati; Sudarshan Singh; Ravish J. Patel (EXCLI Journal : Experimental and Clinical Sciences, 2023)
Phytopharmaceuticals, derived from plants, are increasingly recognized for their potential therapeutic benefits. However, their effectiveness is often hindered by challenges such as poor bioavailability, stability, and targeted delivery. In this study, we aimed to address these limitations by developing PCL (phosphatidylcholine) fortified nano-phytopharmaceuticals to enhance therapeutic efficacy. PCL, a biocompatible and biodegradable polymer, was employed to encapsulate the phytopharmaceuticals, thereby improving their stability and bioavailability. The encapsulation process utilized nanoprecipitation, resulting in the formation of nanoparticles with controlled size and morphology. Various analytical techniques were employed to characterize the physicochemical properties of PCL fortified nano-phytopharmaceuticals, including dynamic light scattering, scanning electron microscopy, and Fourier-transform infrared spectroscopy. Furthermore, the release kinetics of encapsulated phytopharmaceuticals from PCL nanoparticles were evaluated, demonstrating sustained and controlled release profiles, essential for prolonged therapeutic effects. Cytotoxicity studies conducted on in vitro cell culture models confirmed the biocompatibility and non-toxic nature of the developed nano-phytopharmaceuticals. Additionally, in vivo studies were conducted to assess the therapeutic efficacy of PCL fortified nano-phytopharmaceuticals in animal models. The results showIased improved bioavailability, targeted tissue distribution, and enhanced therapeutic effects compared to free phytopharmaceuticals. Moreover, the developed nano-phytopharmaceuticals exhibited prolonged circulation time in the bloodstream, enabling improved drug delivery and reduced dosing frequency. This review highlights the promising potential of PCL fortified nano-phytopharmaceuticals as an effective approach for enhancing the therapeutic efficacy of phytopharmaceuticals. The improved stability, bioavailability, sustained release, and targeted delivery achieved through this formulation strategy offer promising opportunities for advancing plant-based therapies.